Chelation controlled regiospecific O-substitution of myo-inositol orthoesters: convenient access to orthogonally protected myo-inositol derivatives - Devaraj, Subramanian; Shashidhar, M. S.; Dixit, Shailesh S. (Tetrahedron, 2005)
A general method for the completely regioselective protection of the three secondary hydroxyl groups of orthoester derivatives of myo-mositol, utilizing the subtle differences in reactivity exhibited by its alkali metal alkoxides due to differences in their ability to form chelates, is described. This method provides convenient access to orthogonally protected myo-inositol derivatives. A comparison of the methylation of racemic 4-0-trityl-myo-inositol 1,3,5-orthoformate in the presence of sodium or lithium ions showed that stabilization of the C4-alkoxide by chelation with lithium overrides steric hindrance offered by the C6-axial substituent in deciding the regioselectivity during the nucleophilic O-substitution. (C) 2004 Elsevier Ltd. All rights reserved.

O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Regioselective O-acylation of myo-inositol 1,3,5-orthoesters: dependence of regioselectivity on the stoichiometry of the base - Sureshan, Kana M.; Devaraj, Subramanian; Shashidhar, Mysore S. (Tetrahedron, 2009)
A metal mediated unusual 1-3 acyl migration from C4-O to C2-OH of myo-inositol 1,3,5-orthoformate was observed during the alkylation of racemic 4-O-benzoyl-myo-inositol 1,3,5-orthoformate. This has been exploited for the selective esterification of either the C4(6)-OH or the C2-OH of myo-inositol by varying the amount of the base used. While the use of 1 equiv of the base (sodium hydride or potassium tert-butoxide) for the acylation of myo-inositol orthoesters gives the corresponding C4-ester exclusively, the use of two or more equivalents of base for the same reaction gives the C2-ester exclusively. The relatively higher stability of the alkoxide of racemic 2-O-acyl-myo-inositol 1,3,5-orthoester as compared to the alkoxide of 4-O-acyl-myo-inositol 1,3,5-orthoester is suggested to be responsible for the observed isomerization. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Cyclitol; Inositol; Orthoester; Regioselectivity; transesterification

Relative reactivity of hydroxyl groups in inositol derivatives: role of metal ion chelation - Devaraj, Subramanian; Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Carbohydrate Research, 2009)
O-Alkylation of myo-inositol derivatives containing more than one hydroxyl group via their alkali metal alkoxides (sodium or lithium) preferentially occurs at a hydroxyl group having a vicinal cis-oxygen atom. In general the observed selectivity is relatively higher for lithium alkoxides than for the corresponding sodium alkoxide. The observed regioselectivity is also dependent on other factors such as the solvent and reaction temperature. A perusal of the results presented in this article as well as those available in the literature suggests that chelation of metal ions by inositol derivatives plays a significant role in the observed regioselectivity. Steric factors associated with the axial or equatorial disposition of the reacting hydroxyl groups do not contribute much to the outcome of these O-alkylation reactions. These results could serve as guidelines in planning synthetic strategies involving other carbohydrates and their derivatives. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbohydrate; Chelation; Cyclitol; Inositol; Protecting group